1969
DOI: 10.1113/jphysiol.1969.sp008865
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal column projection of fibres from the cat knee joint

Abstract: 1. Stimulation of the cervical dorsal columns excited an average of nine knee joint fibres in the cat posterior articular nerve, eleven fibres in the cat medial articular nerve and thirteen fibres in the monkey posterior articular nerve. 2. Joint fibres projecting to cervical levels were shown to be rapidly adapting by recording with micro‐electrodes from single fibres in intact cat posterior articular nerves. The numerous slowly adapting fibres could not be antidromically excited from the cervical dorsal colu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

1973
1973
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 22 publications
2
26
0
1
Order By: Relevance
“…It is known that cells in the gracile nucleus (Williams, BeMent, Yin & McCall, 1973) and somatosensory thalamus (Yin & Williams, 1976) respond to movements of the knee joint after surrounding skin and muscle have been denervated; these responses are almost entirely rapidly adapting. This is consistent with the finding that the few knee joint afferents which reach the dorsal column nuclei are rapidly adapting (Burgess & Clark, 1969). It appears that slowly adapting knee joint afferents make synaptic contact with cells of Clarke's column (Lindstr6m & Takata, 1972) and project via the dorsal spinocerebellar tract and its collaterals to nucleus z, just rostral to the gracile nucleus -although cells in nucleus z which receive joint input do not appear to relay to the ventrobasal thalamus (Johansson & Silfvenius, 1977).…”
Section: Introductionsupporting
confidence: 92%
“…It is known that cells in the gracile nucleus (Williams, BeMent, Yin & McCall, 1973) and somatosensory thalamus (Yin & Williams, 1976) respond to movements of the knee joint after surrounding skin and muscle have been denervated; these responses are almost entirely rapidly adapting. This is consistent with the finding that the few knee joint afferents which reach the dorsal column nuclei are rapidly adapting (Burgess & Clark, 1969). It appears that slowly adapting knee joint afferents make synaptic contact with cells of Clarke's column (Lindstr6m & Takata, 1972) and project via the dorsal spinocerebellar tract and its collaterals to nucleus z, just rostral to the gracile nucleus -although cells in nucleus z which receive joint input do not appear to relay to the ventrobasal thalamus (Johansson & Silfvenius, 1977).…”
Section: Introductionsupporting
confidence: 92%
“…However, none of DSCT neurones of the muscle group was found to receive excitatory inputs from more than one muscle nerve (but, cf. Mann, 1971 (Brown, 1968;Burgess & Clark, 1969a;Whitehorn Cornwall & Burgess, 1971). The presence or absence of activation of a DSCT neurone by antidromic stimulation of the dorsal column apparently depended on the source of the peripheral sensory input to the neurone (Table 1).…”
Section: Responses To Electrical Stimulation Of Nervesmentioning
confidence: 99%
“…This behaviour was consistent with a lack of activation of these DSCT neurones by antidromic stimulation of the dorsal column (Table 2). It has been shown that rapidly adapting joint receptors are characterized by the fibre projection to the cervical cord through the dorsal column, whereas slowly adapting joint receptor fibres have no direct projection to the high level of the spinal cord (Burgess & Clark, 1969a Methods). The site of recording was marked only when the extracellular response showed a biphasic configuration (soma response, see above) with peak-to-peak amplitude in excess of 2 mV.…”
Section: Responses To Electrical Stimulation Of Nervesmentioning
confidence: 99%
“…는 전방십자인대의 기 동물을 이용한 십자 인대의 감각신경섬유에 대한 동물적 연구는 종종 보고되고 있으나 [6][7][8][9][10] , 인체의 전방십자인대의 감 각신경섬유에 대한 연구는 전방 십자인대 조직의 습득이 어렵 기 때문에 드물다 11,12) . 그리고, 보고된 결과를 살펴 보면, Zimny 등 (Table 1).…”
unclassified